Operation of Conventional Power Plants During the German Energy Transition: A Mini Review - Hanel, Andreas; Fendt, Sebastian; Spliethoff, Hartmut (Frontiers in Energy Research, 2022)
Several unforeseen events have affected the energy market in recent years, both on the consumer side and on the primary energy supply side. Once again, the question is being asked, which impact conventional power plants can have on Germany's energy transition. In this work various energy system studies from the last four years are evaluated, covering a time span of 30 years. Summarized, most studies expect an increasing use of natural gas, peaking in the years between 2030 and 2035. While the overall gross electricity generation from conventional power plants decreases, the share of synthetic energy carries will increase from around zero until 2040 to 100 % in 2050. Hereby the technologically openness of the used energy system model strongly influences the final installed capacities. While more open simulations lead to a median of about 50 GW in 2050, more restrictive ones expect roughly 30 GW. However, the full load hours will decrease significantly in both cases. Since the synthesis of synthetic energy carriers requires large amounts of renewable electricity, this development is linked to a national electricity demand of over 200 TWh for power-to-x applications and an additional import of 350 TWh of power-to-x products.